From Mendel's peas to genetic fingerprinting : discovering inheritance - Morgan, Sally (Chain reactions, 2006)
Examines the history of advances in genetics and some of the important developments in the field, including the discovery of chromosomes and DNA, the human genome project, and genetic fingerprinting.